Discourse an interactive museum for media, information, and communication through an embodied approach - Real, Justine T.; Richelle Rhea R. Baria (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
This CDP addresses one of the most pressing problems globally and the most divisive in our country -- information disorder, a collective term used for disinformation, misinformation and malinformation. The development in media and information technology has and continuously shapes the media landscape in the Philippines particularly with how information is produced, distributed, and consumed. Despite these developments and wealth of local media content and information, there are no memory institutions in the country that specifically highlights Philippine mass media, its histories and narratives which makes Filipinos more susceptible to 'fake news'.

This comprehensive design project proposes an interactive museum to address information disorder which explores embodiment as a theory and develops an embodied approach to architecturally design museum spaces, facilities, and galleries as a tangible solution to the abstract, ephemeral problem that is information disorder. The design concepts echo journalistic themes while the museum's curatorial concept explores the role of media in shaping everyday lives. As the curation for a museum for media, information, and communication has been without precedent until this comprehensive design project, it is suggested to build upon the curatorial findings of this CDP to better improve the architectural process and design development of a museum for media, information, and communication to enhance user experience and architectural quality.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Communication in museums -- Philippines; Museums -- Philippines; Mass media